Epidemiology of esophageal cancer--an overview article - Kollárová, Helena; Máchová, Lucie; Horáková, Dagmar; Janoutová, Gabriela; Janout, Vladimír (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2007)
BACKGROUND: Esophageal cancer is one of the most serious tumor diseases worldwide, owing to its rapid development and fatal prognosis in most cases. To compare epidemiologic characteristics, data published by the International Agency for Research on Cancer, Lyon, France and data from Masaryk Memorial Cancer Institute, Brno, Czech Republic were used. METHODS: We conducted a search of selected Czech and foreign literature focused on the epidemiology of esophageal cancer and its main risk factors. RESULTS AND CONCLUSION: An overview of esophageal cancer epidemiology is presented. Prevention of esophageal cancer should be based on early detection and surveillance of precancerous lesions, especially of Barrett's esophagus, and attention should also focus on modification of changeable risk factors, including tobacco smoking, alcohol abuse, and ingestion of hot and spicy food. Carefully designed epidemiologic studies, both descriptive and analytical, are required to increase understanding of the complexity of esophageal cancer etiology.
Keywords: Czech Republic; lidé; Incidence; Esophageal Neoplasms; incidence; Humans; Česká republika; nádory jícnu